Loneliness in Pre and Post-operative Cancer Patients: A Mini Review - Rokach, Ami (Ital Publication, 2019)
This review explored the experience of hospitalization and the experience of cancer patients who were undergoing Ear Nose and Throat [ENT] surgery. Hospitals, which were designed with treatment and healing in mind, are known to be the source of uncontrollable noise, physicians who talk in a language that patients do not understand. Entering the hospital as a patient, one becomes part of that very complex system, which may include being treated as a ‘nonperson,’ not getting enough information, and losing control of daily activities. Hospitalized patients’ social contact is limited to interaction with the medical staff which thus become a key factor in determining the quality of care, and whether the patients can successfully cope with the stress of their hospitalization experience.Loneliness was found to be associated with a range of negative physical health outcomes such as dementia, increased blood pressure, suicidal thinking and unhealthy and damaging behaviors such as smoking, excess alcohol consumption and lack of exercise leading and contributing to increased mortality. Being, both, hospitalized and in the midst of a frightening illness they experience loneliness and isolation.